Zur Effizienz landwirtschaftlicher Unternehmen in Brandenburg: Eine Data Envelopment Analysis; On the efficiency of farms in Brandenburg - A data envelopment analysis - Alfons Balmann; Britta Czasch (Agrarwirtschaft: Zeitschrift für Betriebswirtschaft, Marktforschung und Agrarpolitik, 2001)
– The transition of East German agriculture led to major structural adjustments that showed some very particular phenomena. For instance, most of the successors of the former agricultural production cooperatives (LPGs) make slight losses and they operate at a higher employment level than new and re-established farms. In this paper we try to explain these phenomena with the farms' history prior to the transition period. Particular attention is given to sunk costs, the identity of members and employees, and old debts. A Data Envelopment Analysis of 210 financial statements distributed over the financial years 1992/93 to 1995/96 gives evidence that these historical arguments had a decisive impact on the farms' behaviour. However, this impact decreases over time, particularly because of a gradual replacement of assets.
Keywords: 330; Landwirtschaft; Effizienz; Data-Envelopment-Analyse; Brandenburg